2009
DOI: 10.1111/j.1471-4159.2008.05865.x
|View full text |Cite
|
Sign up to set email alerts
|

PAL31 may play an important role as inflammatory modulator in the repair process of the spinal cord injury rat

Abstract: Abbreviations used: aFGF, acidic fibroblast growth factor; Anp, acidic nuclear protein; ED1, ectodermal dysplasia 1; GFP, Green Fluorescent Protein; IEF, isoelectric focusing; IFN-c, interferon-c; IL-1, interleukin-1; iNOS, inducible nitric oxide synthase; IpG, immobilized pH gradient; LPS, lipopolysaccharide; MCP-1, macrophage chemoattractant protein 1; NO, nitric oxide; NOS, nitric oxide synthase; PAL31, proliferation related acidic leucine-rich protein; PKA, protein kinase A; SCI, spinal cord injury; SDS-PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Inflammatory response contributes a lot in the regulation of SCI pathogenesis, and seems to play a pivotal role in nerve injury and regenerative response [8]. In addition, inflammatory response may contribute to the apoptosis of neurons and oligodendrocytes as well as to the loss of neuronal function [9]. Therefore, anti-inflammation is thought to be critical for decrease of secondary degeneration and the functional deficit following SCI.…”
Section: Original Papermentioning
confidence: 99%
“…Inflammatory response contributes a lot in the regulation of SCI pathogenesis, and seems to play a pivotal role in nerve injury and regenerative response [8]. In addition, inflammatory response may contribute to the apoptosis of neurons and oligodendrocytes as well as to the loss of neuronal function [9]. Therefore, anti-inflammation is thought to be critical for decrease of secondary degeneration and the functional deficit following SCI.…”
Section: Original Papermentioning
confidence: 99%
“…In our previous study, PAL31 was found to express in the infiltrated macrophages in the epicenter of the injured spinal cord [15]. The amount of PAL31 reached its peak level over 6 days after transection of spinal cord.…”
Section: Resultsmentioning
confidence: 87%
“…Previously, we had identified a phospho-motif in PKA substrates that correlated with SCI rat neural regeneration [15]. This novel molecule was identified as a proliferation related acidic leucine-rich protein (PAL31) with molecular weight of 31 kDa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After SCI, inflammation is a major response and source of secondary injury, considering that it modulates the pathogenesis of acute and chronic SCI [36]. Inflammatory responses cause apoptosis of neurons and glia, as well as glial scar formation and the decline of neuronal function [37]. Pro-inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β), are expressed by CNS cells, including microglia, astrocytes, neurons, and oligodendrocytes at early time points (one to three hours) after SCI [38,39,40].…”
Section: Spinal Cord Injurymentioning
confidence: 99%